Representations of space and public policies linked to a conflict over access to habitat in the city of Tandil (Huellas, 2026)
This article aims to analyze the stance taken by different State agencies in relation to a conflict involving a collective land occupation in the city of Tandil. This event is not an isolated case, since in recent years various indicators show that difficulties in accessing adequate housing have increased for a growing proportion of the population, while speculative processes related to real estate have also intensified. In this regard, the purpose of the article is to explore the complexity that public policy acquires when it requires the coordination of different agencies and levels of the State to address problems of this kind. Furthermore, it seeks to identify discourses that foster representations of space which contribute to the reproduction of social inequalities. The methodology consisted of qualitative techniques, particularly participant observation and documentary sources.
Keywords: Conflicts over access to housing; Popular neighborhoods; Spatial representations; Right to the city; Tandil